2007
DOI: 10.1016/j.otohns.2006.11.018
|View full text |Cite
|
Sign up to set email alerts
|

One‐Year Results: Palatal Implants for the Treatment of Obstructive Sleep Apnea

Abstract: Patients initially responding to palatal implants with improved AHI maintained improvement through long-term follow-up at 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Only FRIEDMAN et al [252] included more obese patients (BMI ,40 kg?m -2 ). The six case series showed a reduction of the AHI .50% and postoperative AHI ,10 in 15-50% of the cases 3-15 months after the procedure [250][251][252][253][254]. Both randomised, placebocontrolled, double-blind studies show a superiority of implants over placebo.…”
Section: Overview Of the Evidencementioning
confidence: 89%
“…Only FRIEDMAN et al [252] included more obese patients (BMI ,40 kg?m -2 ). The six case series showed a reduction of the AHI .50% and postoperative AHI ,10 in 15-50% of the cases 3-15 months after the procedure [250][251][252][253][254]. Both randomised, placebocontrolled, double-blind studies show a superiority of implants over placebo.…”
Section: Overview Of the Evidencementioning
confidence: 89%
“…Recently, there have been several studies investigating the efficacy of palatal implants in OSA patients. Apart from prospective case series with longer follow-up periods [9,10], there have been two placebo-controlled trials undertaken in the United States [4,13]. In those trials, the results regarding the effects on objective outcome measures are conflicting, although they both demonstrated a superiority of palatal implants over placebo.…”
Section: Introductionmentioning
confidence: 99%
“…The results in this study were comparable with previous studies. Nordgård et al [25] showed that 50% of 26 patients had at least 50% reduction to an AHI less than 10 events per hour after follow-up for 1 year. Walker et al [26] revealed that were no obvious factors that predicted the long-term results of OSA after this procedure in previous studies.…”
Section: Discussionmentioning
confidence: 99%